Relations between universals,or divine laws? - Swinburne, R (Taylor and Francis, 2007)
Armstrong's theory of laws of nature as relations between universals gives an initially plausible account of why the causal powers of substances are bound together only in certain ways, so that the world is a very regular place. But its resulting theory of causation cannot account for intentional causation, since this involves an agent trying to do something, and trying is causing. This kind of causation is thus a state of an agent and does not involve the operation of a law. It is simpler to suppose that non-intentional causing is also causing by substances (and not events) in virtue of their powers to act. That raises again the question of why their powers are bound together only in certain ways. The most probable answer is that God, the simplest kind of person there could be, brings this about because it is necessary for the existence of finite rational creatures such as ourselves.